Research on non-timber forest products in selected countries in Southern and East Africa: themes, research issues, priorities and constraints - Ruíz Pérez, M.; Broekhoven, A.J.; Aluma, J.W.R.; Iddi, S.; Lowore, J.D.; Mutemwa, S.M.; Odera, J.A. (1997)
In this paper, the outcomes of a consultative meeting on non-timber forest products are reported and discussed. The meeting was organised by CIFOR and IUCN's Eastern Africa Regional Office on 15 and 16 September 1995 in Nairobi, Kenya, with the aim of discussing research priorities and information gaps related to non-timber forest products. The workshop brought together 11 people, representing forest research institutions, NGOs and other organisations involved in research related to non-timber forest products. The countries represented were Malawi, Kenya, Tanzania, Uganda and Zambia. During the meeting priority themes and issues were identified. These relate to management systems, policy and institutions, and community roles and social dimensions. Priority constraints include lack of personnel with appropriate expertise, inadequate financial resources, and insufficient data and information. A large number of solutions to overcome these constraints was discussed. It is concluded that since the main relevance of non-timber forest products in Southern and East Africa is at the local and subsistence level, an elaboration of the results of the meeting into workable research questions and methods should be defined at that level in an iterative process of action research, involving researchers and local users and managers of the forest. The meeting can be considered as a first, though authoritative, approximation of the needs in research on non-timber forest products in the region. It was agreed that elaboration of the findings of the meeting into specific action would be the only useful next step.